A systematic mapping study of micro-grid architectures - Mera Paz, Julián Andrés; Colmenares Quintero, Ramón Fernando; Maestre Gongora, Gina Paola (Scientia et Technica, 2019)
Introduction: Generation and energy consumption are a major issue in different countries around the world. Nowadays, projects under development seek the modernization of electric power generation and distribution systems. One of the main strategies is the design of context-adaptable micro-grid architectures. The micro-grid concept focuses on a controlled, monitored and highly autonomous use of electric power supported on information technologies, for the optimization of energy transfer, minimize risks and increase the system’s quality, efficiency and reliability. Goal: This article, therefore, aims to identify, classify and compare different micro-grid architectures, based on their applicability and research trends. Method: A systematic mapping study of micro-grid architectures is conducted to examine the experimental and theoretical contributions made by the scientific community. Results: This article categorizes and quantifies the different studies related to the subject, identifying and analyzing the strengths and opportunities for improvement in the applicability of micro-grid architectures. The trends observed highlight five strategies as the most relevant, whose different characteristics contribute to an automated and intelligent organization of the distribution, control and supervision of electricity according to supply versus demand.